2020
DOI: 10.1136/bmjopen-2020-041285
|View full text |Cite
|
Sign up to set email alerts
|

Is education or income associated with insufficient fruit and vegetable intake among cancer survivors? A cross-sectional analysis of 2017 BRFSS data

Abstract: ObjectivesPrevious studies found that low education or income level was associated with insufficient fruit and vegetable consumption (IFVC) among the general population. However, cancer survivors can be heterogeneous from the general population in many aspects. Our objective was to disentangle their association among cancer survivors.DesignNationwide cross-sectional survey in the USA.Setting2017 Behaviour Risk Factor Surveillance System.Participants5409 cancer survivors.Exposure and outcomeEducational level (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
1
3
1
Order By: Relevance
“…We did not have data on type of cancer to be able to estimate weighted percentages among breast cancer survivors solely. Another more recent study using the 2017 BRFSS found that 11.5% of cancer survivors ate 5 or more servings of fruits and vegetables per day [16], a slightly lower weighted percentage than we found in the 2019 BRFSS (15.1% for all cancer survivors). Differences in fruit and vegetable intake reported across different years of BRFSS may reflect actual differences in intake across years, but also may be partially due to differences in wording of survey questions or the different choices by investigators of which fruits and vegetables to include in the total fruit and vegetable variable.…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…We did not have data on type of cancer to be able to estimate weighted percentages among breast cancer survivors solely. Another more recent study using the 2017 BRFSS found that 11.5% of cancer survivors ate 5 or more servings of fruits and vegetables per day [16], a slightly lower weighted percentage than we found in the 2019 BRFSS (15.1% for all cancer survivors). Differences in fruit and vegetable intake reported across different years of BRFSS may reflect actual differences in intake across years, but also may be partially due to differences in wording of survey questions or the different choices by investigators of which fruits and vegetables to include in the total fruit and vegetable variable.…”
Section: Discussioncontrasting
confidence: 93%
“…As mentioned, we did not have information on time since cancer diagnosis, but observed a similar higher prevalence of adhering to multiple behaviors among older cancer survivors (≥ 65 years) compared to younger. We also noted higher prevalence of adhering to multiple behaviors among males, non-Hispanic White and Other race and ethnicity respondents, and those with higher income or education (at least some college) which also have been reported for individual health behaviors in previous studies [15][16][17].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations